PENGARUH SERVICE QUALITY, PERCEIVED VALUE DAN IMAGE TERHADAP CUSTOMER LOYALTY PADA THE ULIN VILLAS AND SPA SEMINYAK - Putu Afry Ardani; Anak Agung Putu Agung; I Made Surya Prayoga (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2021)
Customer loyalty is a strong commitment to subscribe to a particular product or service in the future even though there are situations and competitors that cause changes in consumer behavior. Loyalty is important in the continuity of a company's life, so this study aims to identify the factors to create loyal customers at The Ulin Villas and Spa. Service Quality, Perceived value and Image are factors that influence customer loyalty. The population in this study were customers who had stayed at The Ulin Villas and Spa. The sample in this study used a non-probability sampling technique by means of purposive sampling with a total of 119 respondents. The data was collected through a questionnaire using multiple regression analysis techniques with the help of the SPSS 23 program. The results of this study indicate that Service Quality has a positive and significant effect on customer loyalty, Perceived Value has a positive and significant effect on customer loyalty and has a positive and significant effect on customer loyalty at The Ulin Villas and Spa.